A gateway to more productive research on e‐cigarettes? Commentary on a comprehensive framework for evaluating public health impact. (22nd July 2016) - Brown, Jamie
Abstract : Commentary to:A framework for evaluating the public health impact of e-cigarettes and other vaporized nicotine products